Occurrence and human exposure risk assessment of brominated and organophosphate flame retardants in indoor dust in Ha Noi, Viet Nam - Hoang Thi Tue Minh; Duong Thi Hanh; Phan Quang Thang; Trinh Thu Ha (Vietnam Journal of Science and Technology, 2023)
The widespread use of flame retardants in commercial and industrial products has led to their increased presence in the environment. Recently, indoor dust has been identified as a major human exposure route for flame retardants. In the present study, brominated flame retardants (BFRs) and organophosphate flame retardants (OPFRs) were examined in indoor dust samples collected from apartments in Hanoi, Vietnam. OPFRs were detected at the highest concentrations with the mean concentration of ∑OPFRs was 8700 ng/g (ranged from 1400 to 18000 ng/g). Tris(1-chloro-2-propyl) phosphate (TCPP) and tris(2-butoxyethyl) phosphate (TBOEP) were the most abundant OPFRs in all indoor dust samples, accounting for 50 % (ranged 22 – 69 %) and 33 % (ranged 16 – 63 %) of the total OPFRs levels, respectively. The mean concentrations of total polybrominated diphenyl ethers (PBDEs) and total novel brominated flame retardants (NBFRs) in these samples were 200 ng/g (ranged 67 - 480 ng/g) and 310 ng/g (ranged 56 - 1500 ng/g), respectively. Polybrominated diphenyl ether congener 209 (BDE 209) and decabromodiphenyl ethane (DBDPE) were the most predominant components in PBDEs and NBFRs, respectively. Other BFRs were only found in some samples at very low levels. The estimated daily intake doses (IDs) of FRs via dust ingestion were calculated for both adults and children. The results revealed that the estimated levels of compound exposure through dust ingestion, even under the high-exposure scenario were also below their reference dose (RfD) values, indicating that human health risks from exposure to flame retardants (FRs) via indoor dust ingestion are not significant.